Limited Midline Myelotomy for Intractable Visceral Pain: Surgical Techniques and Outcomes. Issue 4 (18th November 2017) - Vedantam, Aditya; Koyyalagunta, Dhanalakshmi; Bruel, Brian Mendoza; Dougherty, Patrick M; Viswanathan, Ashwin
Abstract: BACKGROUND: Limited midline myelotomy targets the midline nociceptive pathway for intractable visceral pain. Multiple techniques are available for limited midline myelotomy; however, outcome data for each technique are sparse. OBJECTIVE: To review our experience with open and percutaneous approaches for limited midline myelotomy for intractable visceral pain. METHODS: Patients who underwent limited midline myelotomy for intractable visceral pain were reviewed. Myelotomy was performed using 3 techniques: open limited myelotomy, percutaneous radiofrequency myelotomy, and percutaneous mechanical myelotomy. Demographic and perioperative clinical data were recorded. In addition to the visual analog scale and Karnofsy performance score, outcomes were categorized as excellent (no pain), good (considerable reduction in pain, not requiring opioids stronger than codeine), fair (minimal reduction in pain, but no change in opioid medication requirement), and poor (no reduction in pain). RESULTS: Eight patients (median age 56.5 yr, 6 females) underwent limited myelotomy. Four patients underwent open limited thoracic myelotomy with excellent pain outcomes. Three patients underwent percutaneous radiofrequency lesioning with fair (n = 1) and poor outcomes (n = 2). One patient underwent percutaneous mechanical lesioning with a good outcome (n = 1). The median duration of follow-up was 11 wk (2-54 wk). Two patients reported minor sensory complications after the procedure. CONCLUSION: In our preliminary experience, outcomes for open limited thoracic myelotomy were superior to percutaneous approaches. Given the limited utilization of this technique, multicenter registries are needed to further evaluate the best surgical technique for limited midline myelotomy.